Sensor Systems for Gesture Recognition II - Saggio, Giovanni (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This second Special Issue was compiled because of the interest demonstrated by the great success of the first Special Issue devoted to "Sensor Systems for Gesture Recognition".We believe this reprint acts as a meaningful window towards "Gesture Recognition" and the related sensors allowing the gathering of necessary data.